Insights from 25 years of oncogenetics: one person’s perspective - Friedman, Eitan (Frontiers in Genetics, 2023)
In early 1995, I established the oncogenetics service at the Genetics Institute of the Sheba Medical Center in Israel. The purpose of this article is to describe the key points and issues that were raised throughout my personal journey since then: physician and public awareness; ethical and legal issues; guidelines for oncogenetic counseling; the development of oncogenetic testing within the unique Israeli reality of the limited spectrum of BRCA1 and BRCA2 mutations; high-risk vs. population screening; and the definition and implementation of guidelines for surveillance of asymptomatic mutation carriers. Since 1995, oncogenetics has been transformed from a rare oddity to a pivotal player, and it represents a successful example of implementing personalized preventive medicine by identifying and providing care and by offering means for early detection and risk reduction for adults who are genetically predisposed to develop a potentially life-threatening disease—cancer in this case. Lastly, I outline my personal vision for the possible way forward for oncogenetics.